2020
DOI: 10.1177/1352458520912379
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament levels are associated with blood–brain barrier integrity, lymphocyte extravasation, and risk factors following the first demyelinating event in multiple sclerosis

Abstract: Background: Increased blood brain barrier (BBB) permeability, CNS inflammation and neuroaxonal damage are pathological hallmarks in early multiple sclerosis (MS). Objective: To investigate the associations of neurofilament light chain (NfL) levels with measures of BBB integrity and central nervous system (CNS) inflammation in MS during the first demyelinating event. Methods: Blood and cerebrospinal fluid (CSF) were obtained from 142 MS (McDonald 2017) treatment-naive patients from the SET study (63% female; ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 29 publications
(41 reference statements)
4
72
0
Order By: Relevance
“…The higher concentration of IgG and IgA observed in patients with MS with increased QAlb, as well as the higher frequency of monocytes, the higher amount of IFNg and the lower frequency of potentially protective Th2 CD4+ T cells might facilitate CNS damage in these patients. Accordingly, our results demonstrate that patients with MS with increased QAlb show significantly higher levels of biomarkers of CNS damage and inflammation such as NF-L and CHI3L1 and support previous studies, in which increased QAlb in patients with MS was found to be associated with atrophy and greater deterioration 7,8 as well as higher levels of serum NF-L. 18 In addition, we identified 10 intrathecal lipid species that are more abundant in patients with MS with increased QAlb.…”
Section: Discussionsupporting
confidence: 90%
“…The higher concentration of IgG and IgA observed in patients with MS with increased QAlb, as well as the higher frequency of monocytes, the higher amount of IFNg and the lower frequency of potentially protective Th2 CD4+ T cells might facilitate CNS damage in these patients. Accordingly, our results demonstrate that patients with MS with increased QAlb show significantly higher levels of biomarkers of CNS damage and inflammation such as NF-L and CHI3L1 and support previous studies, in which increased QAlb in patients with MS was found to be associated with atrophy and greater deterioration 7,8 as well as higher levels of serum NF-L. 18 In addition, we identified 10 intrathecal lipid species that are more abundant in patients with MS with increased QAlb.…”
Section: Discussionsupporting
confidence: 90%
“…38,39 Patients with the highest CSF/serum albumin ratio also had the highest CSF and blood NfL levels, 40,41 suggesting that an altered permeability of the BCB contributes to serum NfL, though this relationship was not observed in all studies. [40][41][42][43] Of note, there is increased disruption of the BBB with aging which may contribute to the increased levels of blood NfL with age-related neurodegenerative diseases. 37 Investigation of the correlation between the NfL levels in CSF and blood was used to establish that blood NfL measurements accurately reflected what was happening in CNS ( Table 3).…”
Section: Csf Versus Blood Quantification Of Nflmentioning
confidence: 93%
“…Explorative works used the ratio between CSF and serum albumin as an estimation of the BBB permeability although this ratio is a marker of blood CSF barrier (BCB) and should be interpreted as such 38,39 . Patients with the highest CSF/serum albumin ratio also had the highest CSF and blood NfL levels, 40,41 suggesting that an altered permeability of the BCB contributes to serum NfL, though this relationship was not observed in all studies 40–43 . Of note, there is increased disruption of the BBB with aging which may contribute to the increased levels of blood NfL with age‐related neurodegenerative diseases 37 …”
Section: Physiological Factors Influencing Blood Nfl Concentrationmentioning
confidence: 99%
“…Blood–brain barrier permeability itself may be a confounder; neurofilament quotient in blood compared to CSF could be selectively increased following periods of inflammation such as that seen in MS relapse, positively skewing blood NfL levels. Two recent studies on this topic in MS patients present conflicting results [ 14 , 15 ].…”
Section: Neurofilament Pathophysiologymentioning
confidence: 99%